(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The presence of depression can give rise to significant distress due to the nature of the illness, ultimately leading individuals to potentially miss out on favorable prospects in life. Consequently, it is imperative to ensure that these individuals have access to various treatment options aimed at mitigating their symptoms. The objectives of this research were to investigate the opportunities for accessing treatment among individuals with depression, to identify the problems and barriers encountered by the individuals with depression in accessing treatment and to create a causal model of accessing mental health services for individuals with depression. This was the quantitative research involving the data collection from 453 individuals with depression. The descriptive statistical analysis, Confirmatory Factor Analysis, Structural Equation Modeling, the AMOS statistical analysis software, and Path Analysis were utilized. The research findings revealed that individuals with depression have unequal opportunities for accessing treatment due to barriers in accessing services. There are causal factors influencing the access to services, including barriers that directly affect mental health policy. Both direct and indirect factors have an influence on accessing services. Social factors have a direct impact on barriers to access mental health services and have both direct and indirect effects on mental health policy and access to services. As for mental health policy, it directly influences the access to mental health services for individuals with depression. In conclusion, the greatest barriers to access services are the limitation of accessibility to equality, segregation in the access to physical and mental health, shortage of psychiatric doctors and social stigma. These barriers directly and indirectly affect access to mental health services for people with depression. Thus, the solution is to minimize these barriers.